Rapid Detection of Bacterial Vaginosis (BV) by BVBlue test (Bangladesh Journal of Medical Microbiology, 2011)
Bacterial vaginosis is the commonest cause of abnormal vaginal discharge in women of reproductive age and require laboratory test for diagnosis . A total 200 women aged 15-45 years with history of abnormal vaginal discharge were included as study population. Fifty women without such history of discharge were taken as healthy control. Three vaginal swab samples were taken from each case and control. These swab samples were subjected to test by conventional methods such as Amsel clinical criteria, Gram stain Nugent method, culture and by newly developed BV Blue test. The results of the BVBlue test were compared with these methods to find out the efficacy of BVBlue test. Rate of detection of bacterial vaginosis (BV) cases was 21.5% by Amsel clinical criteria, 21.0% by Gram stain Nugent method, 21.0% by culture and 22% by BVBlue test among the study population. When comparing with the conventional test and culture, BVBlue test was 100% sensitive and 98% specific. It is rapid, technically simple and is suitable for screening large number of patient in short time where laboratory facilities are not developed. Key words: Bacterial Vaginosis, BVBlue test, Nugent method, Abnormal vaginal discharge. DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8465 BJMM 2011; 4(1): 24-27